Women, culture & politics - Davis, Angela Yvonne, 1944- (New York : Vintage Books, 1990)
"A collection of speeches and writings by political activist Angela Davis which address the political and social changes of the past decade as they are concerned with the struggle for racial, sexual, and economic equality." - Provided by publisher
I. On women and the pursuit of equality and peace -- Let us all rise together: Radical perspectives on empowerment for Afro-American women -- Facing our common foe: Women and the struggle against racism -- We do not consent: Violence against women in a racist society -- Sick and tired of being sick and tired: The politics of black women's health -- Peace is a sister's issue too: Afro-American women and the campaign against nuclear arms -- Slaying the dream: The Black family and the crisis of capitalism (with Fania Davis) -- Women in the 1980's: Setbacks and victories -- II. On international issues -- When a woman is a rock: Reflections on Winnie Mandela's autobiography -- Children first: The campaign for a free South Africa -- Finishing the agenda: Reflections on Forum '85, Nairobi, Kenya -- Women in Egypt: A personal view -- Revolution and womankind: On Clara Zetkin's selected writings -- III. On education and culture -- Imagining the future -- Reaping fruit and throwing seed -- Ethnic studies: Global meanings -- Art on the frontline: Mandate for a people's culture -- Underexposed: Photography and Afro-American history -- Brushstrokes for social change: The art of Rupert Garcia.
"Originally published in hardcover by Random House ... in 1989"--T.p. verso.
Keywords: African American women; African Americans -- Social conditions -- 1975-; Sexism -- United States; Racism -- United States; Sexism; Racism; United States -- Race relations